Current Trends in the Study of Promising Medicinal Plant Species - N. I. Sidelnikov (Регуляторные исследования и экспертиза лекарственных средств, 2024)
This publication presents the views of Nikolay I. Sidelnikov, Academician of the Russian Academy of Sciences, Director of the All-Russian Scientific Research Institute of Medicinal and Aromatic Plants, on the current developments in the cultivation of medicinal plants, the search for and study of herbal drug sources, and the development of herbal medicinal products. The All-Russian Scientific Research Institute of Medicinal and Aromatic Plants carries out comprehensive studies of medicinal plants, including the evaluation of natural resources in the context of environmental management, the development of agricultural technologies, the search for biologically active substances, preclinical pharmacology and toxicity studies, and the development of technologies for the production of active substances and medicinal.